2020
DOI: 10.1038/s41380-020-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale network dynamics in neural response to emotionally negative stimuli linked to serotonin 1A binding in major depressive disorder

Abstract: Serotonergic dysfunction is implicated in major depressive disorder (MDD), but the mechanisms of this relationship remain elusive. Serotonin 1A (5-HT 1A ) autoreceptors regulate brain-wide serotonin neuron firing and are positioned to assert large-scale effects on negative emotion. Here we investigated the relationship between raphe 5-HT 1A binding and brain-wide network dynamics of negative emotion. 22 healthy-volunteers (HV) and 27 medication-free participants with MDD underwent PET using [ 11 C]CUMI-101 (CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In fact, there is still controversy about the relationship between serum S‐100β levels and depression 35–37 . Although anxiety disorder and depression disorder have overlapping biological mechanisms such as decreased serotonin levels in the brain, the changes of neurotransmitters in the brain are not completely consistent 38–40 . Depression disorder is associated with decreased levels of dopamine and norepinephrine, 41,42 while anxiety disorder is associated with increased levels of these substances 33,43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is still controversy about the relationship between serum S‐100β levels and depression 35–37 . Although anxiety disorder and depression disorder have overlapping biological mechanisms such as decreased serotonin levels in the brain, the changes of neurotransmitters in the brain are not completely consistent 38–40 . Depression disorder is associated with decreased levels of dopamine and norepinephrine, 41,42 while anxiety disorder is associated with increased levels of these substances 33,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Although anxiety disorder and depression disorder have overlapping biological mechanisms such as decreased serotonin levels in the brain, the changes of neurotransmitters in the brain are not completely consistent. [38][39][40] Depression disorder is associated with decreased levels of dopamine and norepinephrine, 41,42 while anxiety disorder is associated with increased levels of these substances. 33,43,44 No significant difference was seen in the levels of 5-HT in S100β knockout mice and wildtype controls, while S-100β depletion led to a significant decrease of norepinephrine in the hippocampus (À12%) as well as in the residual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced 5HT1A binding was shown in both MDD and depression in epilepsy. Reduced 5HT1A seems to reflect hippocampal network inhibition mediated by raphe nuclei hypofunction [76]. However, while studies in MDD point towards reduced receptor density than low serotonin levels, studies of depression in epilepsy point towards reduced serotonin levels and serotonin availability.…”
Section: Differences Between Major Depression and Depression In Epilepsymentioning
confidence: 95%
“…[ 11 C] 45 was metabolized into polar radiometabolites that do not cross the BBB and had a measurable free fraction in plasma of baboons and humans, allowing for calculation of the binding potential . In a PET trial with healthy volunteers, [ 11 C] 45 was proved to be a versatile radiotracer for imaging high-affinity 5-HT 1A binding in humans. , In recent years, [ 11 C] 45 has been used in clinical PET studies to explore the changes of 5-HT 1A receptor level in various physiological conditions, such as a study about the effect of citalopram (a selective serotonin reuptake inhibitor) on emotion processing in humans and a quantification study of PET data using simultaneous estimation of the input function; as well as pathological conditions like major depressive disorder, , schizophrenia, lithium treatment response in bipolar depression, and loudness dependence of auditory evoked potentials research in patients with unipolar and bipolar depression . However, PET studies in baboons and healthy participants , showed that [ 11 C] 45 was insufficient in detecting changes in endogenous intrasynaptic serotonin.…”
Section: Pet Ligands For 5-ht1a Receptorsmentioning
confidence: 99%